SMA Human iPSC-Derived Motor Neurons Show Perturbed Differentiation and Reduced miR-335-5p Expression - Murdocca, Michela (Int J Mol Sci, 2016)
Spinal Muscular Atrophy (SMA) is a neuromuscular disease caused by mutations in the Survival Motor Neuron 1 gene, resulting in very low levels of functional Survival of Motor Neuron (SMN) protein. SMA human induced Pluripotent Stem Cells (hiPSCs) represent a useful and valid model for the study of the disorder, as they provide in vitro the target cells. MicroRNAs (miRNAs) are often reported as playing a key role in regulating neuronal differentiation and fate specification. In this study SMA hiPSCs have been differentiated towards early motor neurons and their molecular and immunocytochemical profile were compared to those of wild type cells. Cell cycle proliferation was also evaluated by fluorescence-activated cell sorting (FACS). SMA hiPSCs showed an increased proliferation rate and also higher levels of stem cell markers. Moreover; when differentiated towards early motor neurons they expressed lower levels of NCAM and MN specific markers. The expression of miR-335-5p; already identified to control self-renewal or differentiation of mouse embryonic stem cells (mESCs); resulted to be reduced during the early steps of differentiation of SMA hiPSCs compared to wild type cells. These results suggest that we should speculate a role of this miRNA both in stemness characteristic and in differentiation efficiency of these cells.